Analisis Kualitas Tidur Penduduk Usia Produktif di Indonesia dengan Model Regresi Logistik Ordinal - Nadiya Azhar Mufid; Kismiantini Kismiantini (Indonesian Journal of Applied Statistics, 2024)
The prevalence of poor sleep quality in the productive age population in Indonesia is quite high. This study aims to analyze factors that influence the sleep quality level of the productive age population in Indonesia by an ordinal logistic regression model based on the Fifth Indonesian Family Life Survey (IFLS5). In this study, the response variable used is sleep quality with an ordinal scale of 5 categories and 12 predictor variables with 1 continuous predictor variable that is age and 11 categorical predictors including education, job status, smoking habit, health, gender, marital status, physical activity, religious, depression level, life satisfaction, and economic level with data of 28.743 respondents. The results of this study indicated that the ordinal logistic regression model with proportional odds model was more suitable to be used to analyze the sleep quality level of productive age population in Indonesia than non-proportional odds model. Based on the analysis result, it was found that among 12 predictor variables, variables that had a significant effect on sleep quality level were education, job status, smoking habit, health, age, depression level, life satisfaction, and economic.Keywords: IFLS, sleep quality, ordinal regression, productive age population